Trends, Problems and Challenges in Managing Piracy Threats in The Straits of Melaka (Journal of International Studies, 2020)
The Melaka Straits is one of the busiest straits in the world. Piracy threats and the advent of 9/11 incidents have created pressures to littoral states, Indonesia, Malaysia, and Singapore, to ensure a safe passage and to avoid disruptions of navigation in the Straits. Given the strait's importance to the East-West trade, littoral states have to respond firmly and promptly to these pressures. The article contends that multilateral approach is the best mechanism in dealing with the threats of regional piracy. Yet there are several problems that need to be addressed by littoral states. Problems in getting suitable assets for surveillance and patrolling, the political sensitivity of the issue in some of littoral states, the issue of jurisdiction, the involvement of neighboring maritime agencies in piracy activities, sophisticated communication network that pirates have, complication in building confidence among littoral states and problems in getting methods of cooperation between the respective nations. These need to be dealt with and taken into consideration in combating piracy in the region. The article concludes that those obstacles have to be given priority, a failure of which could undermine efforts to tackle the issue of piracy and could affect regional stability and economic well-being, and subsequently jeopardize the security of nations and the region.